'I don't have a life to live': deaths and UK detention. (January 2015) - Athwal, Harmit
The Institute of Race Relations has over the last twenty-three years been monitoring the 508 deaths in custody in suspicious circumstances of individuals from BME, migrant and refugee communities, which rarely make the headlines and for which no person is ever convicted (to be published as the report Dying for Justice ). Here, in an extract, the author examines the culture of racism and the impact of privatisation and sub-contracting in the detention and deportation of 'failed' asylum seekers. In case after case it exposes how the vulnerable, mentally- and physically-ill are neglected – leading to deaths by self-harm and inadequate treatment. The death during deportation of Joy Gardner, which involved disproportionate and reckless use of force, is examined in depth. The use of equipment of control for those who are clearly fearful of being forcibly returned, remains a vexed issue.